MODIFIKASI CADANGAN PREMI METODE FULL PRELIMINARY TERM PADA ASURANSI JIWA DWIGUNA MODEL DISKRIT - , MH ROESANGGIT P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Life insurance is an effort to reduce the loss risk due to policy holderâs death. In life insurance, policy holder must pay amount of fund periodically to the insurance company which is called premium. And insurance company promises to give amount of fund to the policy holder's family if the policy holder died which is called benefit. Therefore their liability, insurance company must calculate how much the fund they should be prepared if the event occur in the future. The fund which insurance company must prepared is called by reserve premium. There are several method of reserve premium calculation, some of them are prospective method and full preliminary term method. Prospective method produces the gross premium reserve that is less than net premium reserve. By using full preliminary term method, insurance company can produces the gross premium reserve that is equal to net premium. And the premium reserve which produced by full preliminary term method is less than the prospectiveâs premium reserve if the gross premium reserver is less than the full preliminary termâs gross premium.